2023
DOI: 10.3389/fevo.2023.1324932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental factors on vertical distribution of the eukaryotic plankton community in early summer in Danjiangkou Reservoir, China

Sijie Mai,
Yuxiao He,
Weiguo Li
et al.

Abstract: IntroductionEukaryotic plankton plays crucial roles in ecosystem processes, impacting aquatic ecosystem stability. This study focuses on Danjiangkou Reservoir, a canyon lake in central China, that acts as the water source of the Mid-route of the South-to-North Water Diversion Project.MethodsIn this study, high-throughput 18S rDNA gene sequencing was employed to investigate eukaryotic plankton community at four water depths (0.5 m, 5 m, 10 m, and 20 m). The environmental factors including pH, water temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
0
0
0
Order By: Relevance
“…Based on the NMDS result, we found that wetland eco-engineering had a strong effect on the community structure of the phytoplankton and metazooplankton in the FNWP. This is mainly due to changes in the water environmental conditions that have a strong impact on plankton [43]. For example, nitrogen and phosphorus are often identified as limited nutrients for primary productivity because they are vital materials for cell composition and life activities [44].…”
Section: Pattern Of Plankton Community Structure Variation Before And...mentioning
confidence: 99%
“…Based on the NMDS result, we found that wetland eco-engineering had a strong effect on the community structure of the phytoplankton and metazooplankton in the FNWP. This is mainly due to changes in the water environmental conditions that have a strong impact on plankton [43]. For example, nitrogen and phosphorus are often identified as limited nutrients for primary productivity because they are vital materials for cell composition and life activities [44].…”
Section: Pattern Of Plankton Community Structure Variation Before And...mentioning
confidence: 99%